Methodological aspects of universities’ R&D comercialization in Ukraine in the context of the Quаdruplе Hеlіx Model - Nataliya I. Kholiavko; Tetyana Shestakovska (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
The necessity of the formation and development of the mechanism of commercialization of the researches results of HEIs in Ukraine has been substantiated. The present state of the process of commercialization of the researches results of HEIs in Ukraine has been analyzed. The problems and strategic guidelines for improving the mechanism of commercialization of the researches results of HEIs in Ukraine have been identified. The components of the mechanism of commercialization of the researches results of the HEIs in Ukraine in the context of implementation of the "Quadruple Helix" model (HEIs - business - government - civil society) have been determined, which is focused on the integrated management of innovation activity, in particular, on the process of formation, transfer and realization of scientific developments, the creation of high-tech technologies on their basis. The classification of the researches results of HEIs, which are the objects of commercialization, has been offered